Determinants of Decisions To Purchase Halal Cosmetics In Indonesia - Khotimah, Khusnul; Khasanah, Miftakhul (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This research aims to determine the influence of halal awareness, halal brand image, television advertising, and brand ambassadors on purchasing decisions for Wardah cosmetics in Indonesia. Method: The research method uses a quantitative approach. The study population consisted of 200 Muslim women, consumers of Wardah cosmetic products in Indonesia. The research sample consisted of 200 respondents. The research sampling technique used was purposive sampling. Research data were analyzed using path analysis using SmartPLS version 3.3. Research Finding: The findings show that television advertisements significantly impact on purchasing decisions for Wardah cosmetics in Indonesia, followed by halal awareness and brand image. While brand ambassadors also have a positive influence, their impact is the least among the four variables. Theoretical contribution: The R-Square value shows that the decision to purchase Wardah cosmetics in Indonesia is influenced by halal awareness, halal brand image, television advertising and brand ambassadors by 61.8%, while 38.2% is influenced by other variables that are not measured in this study. Practical implication: Television advertising is the most influential variable in purchasing Wardah cosmetics in Indonesia. Despite technological advancements making information easier to access, television advertising remains highly influential. Brand ambassadors can also influence purchasing decisions, but their effectiveness varies based on brand values, consumer awareness, trust, and preferences. Companies should choose ambassadors who align with target consumer expectations. Research limitation: This research was only carried out specifically for Wardah cosmetic products because the Wardah brand is one of the halal cosmetic brands in Indonesia.